The Effect of Video Animation and Classroom Teaching on Increased Knowledge of the Content of the Shield: A Quasy-Experimental Study at Sanggar Belajar Muhammadiyah Aisyiyah, Kuala Lumpur, Malaysia - Assidik, Qarrin Nafisya Rabbany; Syabariyah, Sitti; Nurhayati (The Indonesian Institute of Science and Technology Research, 2025)
The main objective of this study was to analyze the effect of animated and classical video education on improving knowledge in school-age children. Using a quantitative approach, this study utilized a 2-group pre-test post-test quasi-experimental research design, which included a sample size of 42 respondents selected through a purposive sampling technique. Data were collected through questionnaires and then analyzed using the Wilcoxon Signed Ranks Test. The results showed that Asymp Sig2 -tailed was 0.000 so it was <0.05, so the hypothesis was accepted, because the p-value was less than 0.05, there was a significant difference between knowledge before and after the treatment of health education interventions using animated videos and classical. After intervention using animated videos in the intervention group as many as 20 respondents (87%) and classical 4 respondents (21.1%). The study confirms the effectiveness of both methods, with animated videos proving significantly more impactful in enhancing nutritional knowledge. Statistical tests confirmed the efficacy of this intervention, paving the way for future educational strategies to combat nutrition problems among children. The results of this study support the integration of media-based health education into the school curriculum. Incorporating animated videos and classical methods in health education programs.